Risiko Kerja Disadari, Produktivitas Terkendali : Program Penyuluhan dan Pembekalan K3 bagi UMKM Penjahit di Kota Tanjungpinang - MF, M. Yusuf; Hanum, Ulfa; Silalahi, Santa Novita Yosephin (Jurnal Pengabdian Harapan Ibu (JPHI), 2025)
Tailors are at high risk of occupational accidents, hypertension, and musculoskeletal disorders (MSDs) due to prolonged static sitting postures, extended working hours, and unhealthy lifestyles. These conditions negatively affect both productivity and occupational health. This community service program aimed to improve tailors’ knowledge and awareness of Occupational Safety and Health (OSH) through interactive education. The methods included counseling, pre-test and post-test assessments, and evaluation of program success indicators covering OSH application, work behavior awareness, and healthy lifestyle practices. The results showed a significant increase in knowledge scores, with the mean rising from 5.4 in the pre-test to 9.5 in the post-test, a difference of +4.1 points. Program evaluation revealed high achievement in OSH implementation (100%), work awareness (100%), program benefits (100%), and healthy lifestyle awareness (90%). This program proved effective in enhancing tailors’ capacity to understand and apply OSH principles, thereby potentially reducing the risks of occupational accidents, MSDs, and hypertension. In conclusion, the Program of OSH education and provision is a crucial strategy to create a healthier, safer, and more productive working environment for tailors.